Modelling and Optimisation of Dual Fluidisation Bed Gasifiers for Production of Chemicals - P. Arora; A. Hoadley; S.M. Mahajani; A. Ganesh (Chemical Engineering Transactions, 2015)
Biomass gasification is used in a variety of processes that range from heating application to the production of chemicals. Dual Fluidised Bed Gasifiers (DBFG), with their efficient operation and clean output syngas, are being proposed for many such applications. However, each application has a specific input syngas quality requirement. The quality of the syngas is a function of the biomass feedstock used, the gasifier technology employed, and the gasification conditions. A gasifier model can serve as an effective tool in the understanding of the effect of different parameters on the quality and quantity of syngas. Furthermore, these parameters could also be optimised to systematically meet the requirement of syngas. This study presents a kinetic-based compartment model for DBFGs that are developed in ASPEN Plus®. The model takes into account devolatisation, catalytic and homogenous gasification reactions for syngas and tars (using a lumped species approach); it also considers combustion of char and heat transfer through bed circulation. The model results were found to be in good agreement when compared with the operational data of an 8 MW CHP gasifier in Gussing, Austria. Furthermore, Multi-Objective Optimisation using the NSGA-II algorithm was also performed for the DBFG model. The optimisation aim was to derive a set of process conditions that are most favourable for the production of ammonia from syngas.